A study on comparison between 0.5% levobupivacaine and 0.5% ropivacaine in supraclavicular brachial plexus blockade - A randomized clinical trial - M. Raghupraveen Kumar; V.Sreelatha; T.Swathi Priyadarshini; P.V.S.Lavanya (International Journal of Health and Clinical Research, 2021)
Aim: A prospective randomized, double-blind study was undertaken to compare the onset and duration of sensory and motor blocking properties of 0.5% Levobupivacaine and of 0.5% Ropivacaine in supraclavicular brachial plexus block for elective upper limb orthopaedic surgeries. Methodology: After informed consent, 60 ASA class I and II patients of age 18-65yrs posted for elective upper limb orthopaedic surgeries were randomly allocated into two groups so that each group consists of 30 patients from the Department of Anaesthesiology and critical care, at Kurnool Medical College, Kurnool from August 2018 – July 2019. The study was undertaken after obtaining ethical committee clearance.GROUP A-(L) received 0.5%Levobupivacaine(29ml) with 1ml normal saline.GROUP- B(R) received 29ml of Inj. Ropivacaine hydrochloride0.5%. with 1ml normal saline.Results: Patients who had contraindication for brachial plexus block, hypersensitivity or contraindication to study drugs, patients with severe renal, hepatic, respiratory, cardiac disease, neurological, psychiatric or neurological disorders, were excluded from the study. Under aseptic precautions, supraclavicular brachial plexus block was done employing nerve stimulator. The onset of the sensory blockade and motor the blockade, quality of motor blockade, duration of sensory and motor blockade, adverse events and hemodynamic parameters were studied. In two groups, there was no statistically significant difference in the onset of sensory and motor block. When compared in two groups duration of analgesia and duration of motor block was greater in Levobupivacaine group which was statistically significant. Duration of sensory block and duration of motor block was less in Ropivacaine group. There were no adverse events or hemodynamic instability which were statistically significant in two groups. Conclusion: we conclude that 30 ml 0.5% Levobupivacaine for supraclavicular brachial plexus block produces a longer duration of sensory and motor blockade than ropivacaine.